STUDY ON PHYSICAL PROPERTIES OF STERILIZED FRESH FRUIT BUNCH (FFB) AT PT BIO NUSANTARA TEKNOLOGI BENGKULU - Pandu Imam Subidbyo Adib; Santosa Santosa; B. Isril; K. Anwar (BPFP Faperta UNIB, 2017)
The objective so this research were: (1) to describe the profile of physical properties of sterilized FFB,(2) to find the model describing the performance so sterilization, and (3) to determine the right sterilization duration in respect to FFB ripening levels. This experiment was conducted in PT Bio Nusantara Teknologi Bengkulu by employing a horizontal type of sterilizer; done by following a completely randomized block design with the duration so sterilization as the blocks. Multiple-linear regression analysis was applied to describe the effect of the free variables on the physical property of FFB representing indicators efficacy of conducted sterilization operation. a result of the research indicated that size of weight, level of fruit maturity and duration of sterilization had effects on physical properties of sterilized FFB. Model of prediction describing the effect were as follows: Y(Evaporation)=5,18-0,042X1-0,012X2+0,082X3; Y(Fruit lose,g)=1629,96+8,14X1-3,22X2-10,22X3 ; Y(Amount of kernel damaged) =-1,515-0,06X1+0,035X2 +0,115X3. The proper Sterilization time for a small, unripe FFB was 95 minutes with score 3; for a small, ripe FFB was 95 minutes with score 3; for a small, overripe FFB was 85 minutes with score 3.The appropriate sterilization duration for a big, unripe FFB was 105 minutes with score 3; for a big, ripe FFB was 105 minutes with score 3 and for big overripe FFB was 85 minutes with score 3.